Intelectual Networks and Circulation of Devekopment Models: the French Technical Cooperation During the Agrarian Reform in Chile (1964-1973) - Duran, Daniela (Revista de Historia Social y de las Mentalidades, 2018)
This article seeks to analyse the ideological context in which a French mission of technical cooperation takes place during the period of implementation of the agrarian reform in Chile (1964-1973). It focuses, on the one hand, on the circulation of specific development models discussed on both sides of the Atlantic at the time, and on the other, on the ideological, political and historic elements that feed into the discussion, namely Social Chistianism and ThirdWorldism. The establishment of intellectual networks and ideological affinities among French and Chilean social actors enabled the arrival of the NGO IRAM (Institut de Recherches et Applications de Méthodes de Développement) to Chile.
Keywords: Chilean Agrarian Reform; French Technical Cooperation; Development Models; Circulation and Networks